2000
DOI: 10.1007/s004170000159
|View full text |Cite
|
Sign up to set email alerts
|

Corneal thickness and corneal endothelium in normotensive subjects with unilateral exfoliation syndrome

Abstract: Normotensive eyes with early EXS did not have quantitative (cell density) or qualitative (variation in cell size, frequency of hexagonal cells) morphological changes in corneal endothelium, but had higher values for IOP and CCT. After correcting IOP for CCT, the E eyes still had significantly higher IOP than the fellow NE eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 27 publications
5
32
1
7
Order By: Relevance
“…Inoue et al reported that CCT of EXS eyes in patients without glaucoma (529±31 μm) was significantly lower than that of control eyes (547±28 μm) [27]. Puska et al however, found CCT to be higher in eyes with EXS than in the fellow eyes without EXS [28]. In the current study, there were no significant differences in CCT between the control eyes and exfoliative eyes with or without glaucoma.…”
Section: Discussioncontrasting
confidence: 57%
“…Inoue et al reported that CCT of EXS eyes in patients without glaucoma (529±31 μm) was significantly lower than that of control eyes (547±28 μm) [27]. Puska et al however, found CCT to be higher in eyes with EXS than in the fellow eyes without EXS [28]. In the current study, there were no significant differences in CCT between the control eyes and exfoliative eyes with or without glaucoma.…”
Section: Discussioncontrasting
confidence: 57%
“…The mean percentage of hexagonal cells in PXG eyes in our study was 50.9 ± 2.47 which was in accordance to previous studies as 54.9 ± 10.9 [35], 56.4 ± 7.5 [35], 57.1 ± 7.1 [36]. The mean central corneal thickness in PXG patients has been reported as 493 ± 33 [37], 507 ± 25 [38], 528 ± 30 [39] which was comparable to our study group 556.4 ± 28.95. In our study there was a significant difference in the CCT in PXG patients compared to the normal group 572.5 ± 19.91.…”
Section: Discussionsupporting
confidence: 91%
“…However, there are conflicting studies about central corneal thickness (CCT) in patients with PXS or pseudoexfoliative glaucoma. Most studies have reported similar CCT in PXS and normal eyes (9)(10)(11)(12)(13) , but some authors have reported a thinner (14,15) or thicker (16,17) CCT in PXS eyes than in normal eyes.…”
Section: Introductionmentioning
confidence: 99%